PENGARUH SUHU PENYIMPANAN DAN WAKTU PENGKONDISIAN UNTUK MEMPERTAHANKAN KUALITAS KENTANG KULTIVAR MARGAHAYU - Asgar, Ali; Rahayu, ST (BERITA BIOLOGI, 2014)
The study aimed to determine the effect of storage temperature and time reconditioning to maintain the quality of potato cultivars Margahayu. The experiments were conducted in the Laboratory of Postharvest of Vegetable Crops Research Institute (BALITSA) from July to October 2012. Altitude research is ± 1200 masl with temperatures between 14.94 - 24.61°C and the relative humidity (rH) 85.56%.Experimental design used in this study was factorial a randomized complete design consisting of 2 factors. Treatments were factorial combinations of storage temperature (4 °C, 7 °C and 10 °C) and time reconditioning (0 days, 3 days, 6 days and 9 days).The number of replications for each treatment was 3. The results of research showed that there is interaction between storage temperature and reconditioning on reducing sugar content and vitamin C. Storage temperature and reconditioning treatments were positive affect on Total Soluble Solid (TSS) and organoleptic chips. The treatment can maintain the quality of the potato tuber is the storage temperature 7 °C, 10 °C with a time of 6 to 9 days reconditioning.